Soluble CD206 plasma levels in rheumatoid arthritis reflect decrease in disease activity. (4th July 2017) - Heftdal, Line Dam; Stengaard-Pedersen, Kristian; Ørnbjerg, Lykke Midtbøll; Hetland, Merete Lund; Hørslev-Petersen, Kim; Junker, Peter; Østergaard, Mikkel; Hvid, Malene; Deleuran, Bent; Møller, Holger Jon; Greisen, Stinne Ravn
Abstract: Rheumatoid arthritis (RA) is characterized by chronic joint inflammation and infiltration by activated macrophages. TNFα is a central mediator in this process. The mannose receptor, CD206, is a scavenger receptor expressed by M2A -macrophages and dendritic cells. It is involved in collagen internalization and degradation. The soluble form has been suggested as a biomarker of M2A -macrophage activation. The aim of this study was to investigate sCD206 plasma levels in early RA patients initiating anti-TNFα treatment. Plasma levels of sCD206 were measured by ELISA in samples from 155 early RA patients with an average symptom duration of 3 months. Patients were randomized to 12 months' methotrexate and placebo (PLA) or methotrexate and adalimumab (ADA) treatment, followed by open-label treatment with disease-modifying anti-rheumatic drugs (DMARD) and if needed, ADA. Disease activity was assessed at baseline and after 3, 6, 12 and 24 months. Baseline plasma level of sCD206 in treatment naïve RA patients was 0.33 mg/L (CI: 0.33–0.38 mg/L) corresponding to the upper part of the reference interval for healthy controls (0.10–0.43 mg/L). In the PLA group, sCD206 levels decreased after 3 months, but did not differ from baseline after 6 months. In the ADA group, however, levels remained lower than baseline throughout the treatment period. In conclusion, initially, plasma sCD206 in early RA patients decreased in accordance with disease activity and initiation of DMARD treatment. Treatment with anti-TNFα preserved this decrease throughout the study period.